From Milltown to Malltown poems - Daniels, Jim 1956- (Marick Press, 2010)
Poems accompanied by photographs of Homestead, Pennsylvania, a former steel mill town now home to numerous chain stores. The new Waterfront mega shopping center contrasts with the declining steel-era part of town
Keywords: Homestead (Pa.) / Poetry; Homestead (Pa.) / Photographs